Big Feelings in a Small Syringe: Exploring Parental Distress in Type 1 Diabetes and the Buffering Role of Child Life Specialists - Singh, Preeti; Gopalan, Sushma; Sastry, Shruti; Bhat, N Kavitha; Ginigeri, Chetan (Indian Journal of Child Health, 2026)
Background: Caring for a child or adolescent with Type 1 Diabetes (T1D) requires sustained emotional, relational, and behavioural involvement from parents and may lead to psychological distress. Although parental diabetes-related distress has gained increasing recognition globally, evidence from Indian paediatric care settings remains limited, where psychosocial services are not routinely integrated into diabetes management. A clearer understanding of the psychological dimensions of parental distress is essential for developing family-centred interventions. Materials and methods: This pilot cross-sectional exploratory study was conducted during a Diabetes Awareness Camp at Aster CMI Hospital, Bangalore. Thirteen parents (eight fathers and five mothers) of children and adolescents with T1D attending a multidisciplinary clinic participated. Parental distress was assessed using the Parent Diabetes Distress Scale (Parent-DDS), a validated psychological instrument evaluating four domains: Teen Management Distress, Parent–Teen Relationship Distress, Personal Distress, and Healthcare Team Distress. Data were analysed using descriptive and exploratory statistical methods. Results: Parents reported a moderate level of overall psychological distress (mean score = 2.60). Distress related to parent–teen interactions was the most prominent domain (mean = 2.73), indicating substantial relational strain associated with diabetes management. The Healthcare Team Distress domain demonstrated the greatest variability (SD = 1.09), reflecting differences in perceived quality of medical communication and support. Approximately 25% of participants had distress scores in the high range (≥ 3.20), indicating clinically meaningful emotional burden. Fathers tended to report higher distress levels than mothers across several domains; however, these differences were not statistically significant. Conclusion: A considerable proportion of parents of children with T1D experience elevated psychological distress, primarily influenced by relational challenges and perceptions of professional support rather than medical factors alone.